Pertanggungjawaban Hukum Notaris terhadap Keabsahan Akta Perjanjian Pengikatan Jual Beli - Koesoma, Arya; Muskibah, Muskibah; Syamsir, Syamsir (Recital Review, 2026)
This study examines the legal liability of notaries concerning the execution of Sale and Purchase Agreement Deeds (PPJB) that are misused as a disguise for loan agreements, as reflected in Supreme Court Decision No. 813 K/Pdt/2023. The main issues addressed are the forms of legal responsibility borne by notaries in drafting such deceptive agreements and the extent of legal certainty arising from them. Positioned within the framework of civil and notarial law, this research employs a normative juridical approach by analyzing statutory provisions, legal doctrines, and relevant jurisprudence. The findings reveal that a notary may be held legally accountable civilly, administratively, or ethically if found negligent in examining the true intention and lawful cause of the agreement. A PPJB used to conceal a loan transaction fails to meet the legal requirements of a valid contract due to its unlawful cause and is therefore null and void. This study underscores the significance of the principles of prudence and professional responsibility for notaries to ensure legal certainty and the protection of parties’ rights in every authentic deed they execute.